Perbedaan Sanksi Terhadap Pelaku Prostitusi dalam Peraturan Daerah Kabupaten Bandung dan Qonun Aceh - Agung Cahya Firdaus; Ayu Sentia Rahayu; Fadhlan Surya; Fajria Asfal Asfia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Prostitution is a job that violates immoral work that falls under the act of adultery and is an act that is prohibited by Islam. Regulation of perpetrators of prostitution in the form of sanctions can be seen from two aspects, both the religious aspect and the regional cultural aspect. The sanctions given to perpetrators of prostitution should be enforced in the regions or can be called regional regulations. Prostitution is an act of adultery which is included in the major sins. In the Aceh qonun it is included in 'uqubah hudud', in the Bandung district regional regulations prostitution is included as an offence. Prostitution is a service to provide satisfaction to customers who order it, apart from violating immorality, in this case prostitution is also a place to cause and spread diseases, one of which is AID/HIV, the sanctions for prostitution from each region always have differences, but this aims to prevent and attract benefits. The method used in this research uses a comparative method with a normative juridical approach, the type of data used is descriptive-qualitative data, namely classifying, comparing and connecting. The results of the research show that the sanctions for prostitution in the Bandung Regency regional regulations are in the form of imprisonment for 3 (three) months, or a fine of up to Rp. 5,000,000,- (Five million rupiah. Meanwhile), sanctions for perpetrators of prostitution in the Aceh Qonun are classified as heavy because of the act of prostitution referring to the act of adultery, the punishment that can be imposed for prostitution is 100 (one hundred) canings, or a fine of 1000 (one thousand) grams of pure gold.